Pemaknaan Islam Moderat Sebagai Sebuah Terminologi - Dedi Sahputra (Mahesa Research Center, 2021)
This article aims to find out the meaning of the term moderate Islam as a terminology. The problem is focused on reviewing the language and its history, as well as from the context of the political interests that lie behind it. In order to approach the problem, this article uses a reference to the theory of terminology. The data were collected through a literature review of various similar studies that have been conducted. Furthermore, the data obtained were analyzed qualitatively. This study concludes that there is a bias in understanding the terminology of moderate Islam which lies in equating the word